Analysis of the relationship between oipA, babA2, babB genotypes and helicobacter pylori-related gastric precancerous lesions - Yang, Keke; Shi, Lei; Chen, Jinghua (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the distribution of helicobacter pylori-related genotypes of oipA, babA2, and babB in patients with gastrointestinal diseases. Method: The retrospective study was conducted at the Jiamusi College, Heilongjiang University of Traditional Chinese Medicine, Harbin, China, and comprised data from February 2017 to May 2020 of patients of either gender 20-80 years who underwent gastroscopy. An instrument based on polymerase chain reaction was used to amplify oipA, babA2 and babB genes, and their distribution in terms of gender, age and pathological types was analysed. Results: Among the 116 patients, 52(44.8%) had oipA genotype, 48(41.2%) babA2, and 72 (62.1%) babB, respectively, and the size of amplified products of 486bp, 219bp and 362bp, respectively. The infection rate of oipA and babB genotypes was highest [26(50.0%) and 31(43.1%)]in those aged 61-80 years, and lowest [9(17.3%) and 15(20.8%)]in those aged 20-40 years. The infection rate of babA2 genotype was highest [23(47.9%)] in those aged 41-60 years, and lowest [12(25.0%)] in those aged 61-80 years. Male patients were under a higher [28(53.9%) and 26(54.2%)] rate of infection with oipA and babA2, and female patients has a higher [40(55.6%)] rate of infection with babB. Among Hp-infected patients with digestive diseases, babB genotype was mainly found in patients with chronic superficial gastritis[17(58.6%)], duodenal ulcer[17(85.0%)], chronic atrophic gastritis[19(59.4%)] and gastric ulcer[16(72.7%)], while oipA genotype was mainly found in patients with gastric cancer[8(61.5%)]. Conclusion: Chronic superficial gastritis, duodenal ulcer, chronic atrophic gastritis, and gastric ulcer may have a close bearing on babB genotype infection, while oipA genotype infection may be associated with gastric cancer. Key Words: Helicobacter pylori, oipA, babA2, babB, Chronic superficial gastritis, Chronic atrophic gastritis, Duodenal ulcer, Gastric ulcer, Gastric cancer.